Ответы и объяснения

2012-11-28T17:02:46+04:00

а)4y-(3y-(2y+1))=4y-(3y-2y-1)=4y-(y-1)=4y-y+1=3y+1

б)a-(2x-(2a-x)=a-(2x-2a+x)=a-(3x-2a)=a-3x+2a=3a-3x=3(a-x)

в)3m-(3m+(3m-(m+3)))=3m-(3m+(3m-m-3))=3m-(3m+3m-m-3)=3m-3m-3m+m+3=3-2m

г)b-(2c-(3b+(4c-5b)))=b-(2c-(3b+4c-5b))=b-(2c-3b-4c+5b)=b-2c+3b+4c-5b=2c-b

 

Лучший Ответ!
2012-11-28T17:13:29+04:00

а) 4y-(3y-(2y+1)) = 4y-(3y-2y-1) = 4y-3y+2y+1 = 3y+1

б) a-(2x-(2a-x)) = a-(2x-2a+x) = a-2x+2a-x =3a-3x

в) 3m-(3m+(3m-(m+3))) = 3m-(3m+(2m-3)) = 3m-(3m+2m-3) = 3m-3m-2m+3 = -2m+3

г) b-(2c-(3b+(4c-5b))) = b-(2c-(3b+4c-5b)) = b-(2c-3b-4c+5b) = b-2c+3b+4c-5b = -b+2c